Leviathan or the matter, forme and power of a commonwealth ecclesiasticall and civil - Hobbes, Thomas (Oxford Basil Blackwell, 1960)
Contents: biographical, the context of the Leviathan, the mind and manner, the system, the argument of the Leviathan and some topics considered.
Keywords: Tham khảo